Meta-Analysis of the Incidence, Prevalence, and Correlates of Atrial Fibrillation in Rheumatic Heart Disease - Jean Jacques Noubiap; Ulrich Flore Nyaga; Aude Laetitia Ndoadoumgue; Jan René Nkeck; Anderson Ngouo; Jean Joel Bigna (Ubiquity Press, 2020)
Objective: To estimate the incidence, prevalence, and correlates of atrial fibrillation (AF) in a global population with rheumatic heart disease (RHD). Methods: Bibliographic databases were searched to identify all published studies providing data on AF in patients with RHD. Random-effects meta-analysis method was used to pool estimates. Results: Eighty-three studies were included, reporting data from 75,637 participants with RHD in 42 countries. The global prevalence of AF in RHD was 32.8% (range: 4.3%-79.9%). It was higher in severe valvular disease (30.8% vs 20.7%, p = 0.009), in severe mitral valve disease compared to severe aortic disease (30.4% vs 6.3%, p = 0.038). The global cumulative incidence of AF in patients with RHD was 4.8%, 11.4%, 13.2%, and 30.8% at 1, 2, 5, and 10 years of follow-up, respectively. From comparison between patients with and without AF, AF was associated with increased age (mean difference [MD]: 9.5 years; 95% CI: 7.8-1.3), advanced heart failure (odds ratio [OR]: 4.4; 95% CI 2.1-9.3), tricuspid valve involvement (OR: 4.0; 95% CI: 3.0-5.3), history of thromboembolism (OR: 6.2; 95% CI: 3.4-11.4), highly sensitive C-reactive protein (MD: 5.5 mg/dL; 95% CI: 1.2-9.8), systolic pulmonary arterial pressure (MD: 3.6 mmHg; 95% CI: 0.8-6.3), right atrium pressure (MD: 1.5 mmHg; 95% CI: 1.0-2.0), and left atrium diameter (MD: 8.1 mm; 95% CI: 5.5-10.7). Conclusions: About one-third of patients with RHD have AF, with an incidence which almost triples every five years after diagnosis. Factors associated with AF include age, advanced heart failure, thromboembolism, and few cardiac hemodynamics parameters.